Structural competency in epidemiological research: What's feasible, what's tricky, and the benefits of a 'structural turn' - Ángel Martínez-Hernáez; Deborah Bekele (Taylor & Francis Group, 2023)
Structural competency is an emerging paradigm for both the training of health professionals and the creation of a common language addressing structural processes that determine health disparities. However, its application to the field of epidemiological design and research is absent. Based on our previous proposal of a tool for Structural and Intercultural Competency in Epidemiological Studies, the SICES guidelines, in this article we analyse the possibilities and challenges of a 'structural turn' in epidemiology. In terms of possibilities, we recognise the value of paradigms from multiple parts of the world, such as social and sociocultural epidemiology, critical epidemiology and collective health, in facilitating a structural turn in epidemiological studies. In this framework, structural competency would provide a new angle by focusing not only on what to research (e.g. inequalities), but with what skills and attitudes (e.g. cultural and epistemic humility). The challenges lie in the inclusion of reflexivity and a comprehensive view in the context of a positivist epidemiology oriented towards obtaining evidence from a biomedical, but not social, perspective.